APPLICATION OF GRAVITY AND MAGNETIC TECHNIQUES TO DELINEATE THESUBSURFACE FEATURES IN THE BASEMENT COMPLEX IN IMO BASIN, EASTERNNIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
The  area  of  study  is  situated  in  the  Nige r   Delta .  The  current  study  is  concerned  with  the  analysis  of magnetic   and   gravity   data   aiming   to   evaluate   the   subsurface   structure   of  the   basement   rocks .  The aeromagnetic   and   gravity   methods   of   prospecting   give   an   effective   presentation   of  the   subsurface structures . The aeromagnetic data was corrected and  represented  by total aeromagnetic  intensity  map then was  reduced  to  the  north  magnetic  pole .  The  corrected  gravity  data  is  represented  by  Bouguer anomaly map. The  ﬁltering  techniques  were  applied  to  the  corrected  aeromagnetic  and  gravity  maps to  obtain  the residual  component  caused  by  local  structures  and  anomalies  bodies .  The  integration  of  radially  power spectrum was  applied  on  both  magnetic  and  gravity to  estimate the depths of the shallow sources and the deep sources . The equivalent depths of the isolated short wavelength anomalies are 0.5 km and 0.4 km, and the  depths  of  the  long  wavelength  anomalies  are  3.5  and  3  km  for  the   magnetic  and  gravity   data, respectively. The Euler deconvolution and 3-D modeling were applied to magnetic and grav- itydata . The 3-D Euler  deconvolution  is  used  not  only  to  delineate  major  subsurface  structures  but  also  to  determine  the structural  indices  of them as well as the average  depth  of the  magnetic and gravity  sources . The  calculated structural  indices  show that the  area  is  mainly affected by contacts/thin sheet and the esti- mated  depth  of magnetic  and  gravity  sources   ranged  between  500  m  and   2000  m,   also  the   3-D   Euler  deconvolution showed  that  the  area  was  affected  by  different  fault  trends  such  as  NNE-SSW,  NW-SE and  E-W  trends . The  results  of 3-D  magnetic  and  gravity  interpretation  revealed that the  depth  of base- ment  was  ranging from  2500 m to  3000 m  .The  main tectonic  deformations  of the  area  of study  have NNE-SSW, NW-SE and E-W trends .